Design and optimization of high electron mobility transistor with high-k dielectric material integration - Sreenivasa Rao, Devireddy; Sirisha, Malluri; Srinivas Murthy, Deepthi Tumkur; Krishne Gowda, Nayana Dunthur; Balaji, Bukya; Kiran Kumar, Padakanti (Institute of Advanced Engineering and Science, 2024)
We have developed and simulated a high electron mobility transistor (HEMT) operating in the 5 nm regime. This HEMT uses hafnium oxide (HfO2), a high-k dielectric material, to create an undoped region (UR) beneath the gate. While the gate and undoped regions share equal thickness, the channel length differs. This innovative undoped under the gate dielectric HEMT design mitigates the maximum electric field (V) within the channel area, leading to a significant increase in drain current. The utilization of a high-k dielectric in the HEMT structure results in a saturated Ion current that is 60% higher compared to conventional structures. Specifically, we use an AlGaN/GaN/SiC-based HEMT with an intrinsic section below the gate, using HfO2 as the high-k dielectric substantial, for applications requiring high power and high-frequency power amplifiers. Compare this advanced HEMT design to conventional HEMTs and you will see improved conductivity, a greater drain current (Id), a 54% increase in transconductance (Gm), and a lower on-resistance (Ron). Additionally, advancements in the electric field in the Y direction are seen. This HEMT structure exhibits superior performance compared to alternative materials analyzed. The integration of AlGaN/GaN materials in HEMTs opens up extensive opportunities in the realms of radio frequency very large-scale integration (VLSI) and power electronics.